Michele e Raskol’nikov: Storia di un doppio mancato - Paronzini, Nicole (Romance eReview, 2014)
“Io sono un discepolo di Dostoevskij […] Dostoevskij è il mio maestro, è il maestro di tutti quelli che sono considerati scrittori esistenziali” (“I am a disciple of Dostoevsky […] Dostoevsky is my master: he is the master of all existentialist writers”) – Alberto Moravia. With these words, pronounced during a TV interview, the Italian writer Alberto Moravia (1907-1990) singled out the writer who most deeply influenced his own work. Inspired by these words, I plan to demonstrate the link that exists between the Russian novelist Fyodor Dostoevsky (1821-1881) and Moravia; more specifically, I investigate the influence of Dostoevsky’s Crime and Punishment (1866) on Moravia’s masterpiece Gli indifferenti (1929). This analysis will focus in particular on the theatrical and philosophical dimension of both texts. I will show the elements of continuity, which testify the importance of Dostoevsky’s model, as well as the dissimilarities that exist between these two works, which reveal Moravia’s very personal understanding of Dostoevsky’s genius. One apparent contradiction arises. On the one hand Dostoevsky investigates the most obscure and controversial aspects of human nature, on the other hand Moravia’s characters become symbols of superficiality and indifference: the goal of this paper is to show the connections between these seemingly opposite literary worlds. I will focus in particular on the main characters of the two novels, Raskolnikov (Crime and Punishment) and Michele (Gli indifferenti). Outlining the similarities as well the profound dissimilarities that exist between the two, I shall demonstrate that Michele is nothing but the offspring of Raskolnikov.